Sire evaluation based on first lactation milk yield traits in HF X Gir halfbred - Bhoite, U Y; Mote, M G; Adsul, P B (Indian Journal of Dairy Science, 2020)
The data on first lactation milk production performance of 422, HF X Gir halfbred cows maintained at Research Cum Development Project on Cattle, MPKV, Rahuri were utilized for estimation of least squares means, correlation among the traits and heritability of traits. Breeding values of sires were estimated by REML computer programme. The overall least squares means (kg) of first lactation monthly test day milk yield (from 1st to 6th month) (FLMTDMY), first lactation peak milk yield (FLPMY) and first lactation 300 days milk yield (FL300 DMY) were 10.54 ± 0.14, 10.57 ± 0.13, 10.10 ± 0.12, 9.48 ± 0.12, 8.93 ± 0.11, 8.23 ± 0.11, 14.22 ± 0.14 and 2438.98 ± 38.49 respectively. Phenotypic and genotypic correlations among the traits were positive and significant (P<0.01). Heritability of traits was low to moderate and ranged from 0.06 to 0.25. Sire number HG-412 and HG-129 had highest breeding values for FLMTDMY and H-28I and HG-15 had highest breeding value for FLPMY and FL300DMY and ranked first.